Development of a Cooking, Food Budgeting, and Nutrition intervention for American Indians with Type 2 Diabetes: Rationale and Study Protocol for the Cooking for Healthy Study. (29th May 2020) - Fretts, Amanda; Hawley, Caitie; Brown, Meagan; Ornelas, India; Best, Lyle; McKnight, Barbara; Thorndike, Anne; Hager, Arlette; Beresford, Shirley; Howard, Barbara; Umans, Jason; Huber, Corrine
Abstract: Objectives: Type 2 diabetes is a leading cause of morbidity among American Indians (AIs). Although healthy diet is a key component of diabetes management, many AIs face barriers to adopting a healthy diet. Preliminary work in an AI community in the north-central USA indicated that the most salient factors that influence healthy diet are: difficulty budgeting for food, low literacy/numeracy when purchasing food, and limited cooking skills. The Cooking for Health Study is a randomized controlled trial developed in partnership with the community that will evaluate the efficacy of a culturally-tailored healthy food budgeting, purchasing, and cooking program on: (1) intake of sugar-sweetened beverages and processed foods; and (2) healthy food budgeting and cooking skills, among AIs with diabetes. Methods: The curriculum was informed by focus groups and meetings with community members and in partnership with the tribal diabetes program. The curriculum comprises a 12-month online/distance-learning program delivered through video and written materials. Over one year, we will recruit 165 AI participants with diabetes who are members of the community and reside on the reservation. Individuals will be randomized (using a 1:1 ratio) to intervention or control arm (i.e., delayed intervention). Participants in the intervention arm will receive the curriculum over a year. At baseline, month 6, and month 12, all participants will complete in-person study visits that include food frequency questionnaires, and assessments of food resource management and cooking confidence. Results: The curriculum focuses on cooking and budgeting skills, and optimal diet for diabetes management. Lessons include: getting healthy foods; vegetables; fruits; dairy; protein and meats; grains; food budgeting and meal planning; empty calories; snacking; traditional foods; and celebrations. Each lesson comprises 3–8 videos paired with written materials. Enrollment will commence in early 2020. Conclusions: Poorly controlled diabetes disproportionately affects the health of AIs compared to other racial/ethnic groups, and has profound effects on healthcare costs. Improving healthy food budgeting, purchasing, and cooking skills among AIs with diabetes should improve diet/diabetes management. Funding Sources: NIH/NIMHD R01MD011596.